From understanding to action: a juncture-factor framework for advancing social responsiveness in health professions education - Botha, G. C.; Crafford, L. (Frontiers in Medicine, 2024)
Background: Low-to middle-income countries face critical healthcare challenges. Equipping graduates with social responsiveness, the ability to address community health needs effectively, is essential. Despite its importance, research on integrating social responsiveness principles into medical and pharmacy curricula remains limited. This study explores how understanding of social responsiveness translates to practice in a resourceconstrained context and identifies critical factors for future direction. Methods: Semi-structured focus groups were conducted with curriculum developers, academic staff, and alumni (n=27) using purposive sampling. Thematic analysis yielded an emergent "juncture-factor" framework for integrating SR into curricula. Results: Our analysis revealed a four-stage framework for integrating social responsiveness. It categorizes existing and evolving efforts into four key junctures (points in time) and twelve factors for consideration at each juncture. The Illuminate juncture emphasizes raising awareness, fostering agreement, and aligning institutional values with community needs. The Construct stage focuses on inclusivity, contextualizing learning, developing relevant content, and employing appropriate pedagogy. The Influence juncture ensures validated social responsiveness action, effective implementation, and faculty and student capacity building. Finally, the Coalesce juncture promotes collaboration and internalization of social responsiveness principles among stakeholders. Conclusion: This framework aligns with international social responsiveness literature while offering a unique low-to middle income country perspective. It acknowledges the complexities of integrating social responsiveness and provides practical ways to address them. This framework serves as a valuable tool for curriculum review in resourceconstrained contexts. Future research could explore its applicability across diverse settings, and investigate its long-term impact on student learning and professional development,